HSPB1 Regulates Autophagy and Apoptosis in Vascular Smooth Muscle Cells in Arteriosclerosis Obliterans - Keqin Chen; Changmiao Hou; Lei Xu; Hanwu Peng; Chaogui He; Jing Liu; Guoqing Wang; Shaoshuai Huang; Xiehong Liu (Cardiovascular Therapeutics)
Objective. Small heat shock protein-1 (HSPB1) is a small heat shock protein that participates in many cellular processes and alleviates stress-induced cell injury. Autophagy protects cells from many types of stress and plays a key role in preventing stress in arteriosclerosis obliterans (ASO). However, the roles of HSPB1 in autophagy and apoptosis in the context of ASO pathogenesis remain unclear. Methods. In vivo and in vitro studies were used to determine whether HSPB1 is associated with ASO progression. The expression of HSPB1 was measured in normal and sclerotic blood vessels. The role of HSPB1 and its potential downstream signaling pathway were determined in VSMCs by overexpressing and silencing HSPB1. Results. A total of 91 ASO patients admitted to and treated at our hospital from Sep. 2020 to Sep. 2021 were selected, and plasma HSPB1 expression was assessed. We divided the patients with ASO into the grade I (n=39), II (n=29), III (n=10), and IV (n=13) groups according to Fontaine’s classification. Plasma HSPB1 levels were markedly decreased in patients with grade III (n=10) and IV (n=13) ASO compared with patients with grade I ASO. Furthermore, HSPB1 expression was significantly decreased, and p62 and cleaved caspase-3 were increased in the sclerotic vasculature compared to the normal vasculature (p<0.05). Overexpression of HSPB1 promoted apoptosis of VSMCs following ox-LDL treatment. Knockdown of HSPB1 led to a marked increase in the expression of LC3II and Beclin-1 in ox-LDL-stimulated VSMCs, whereas knockdown of HSPB1 attenuated these changes (p<0.05). Importantly, overexpression of HSPB1 promoted the dephosphorylation of JNK in ox-LDL-stimulated VSMCs. Conversely, downregulation of HSPB1 induced the opposite change. Conclusion. Loss of HSPB1 promotes VSMC autophagy and inhibits VSMC apoptosis, which are associated with ASO. HSPB1 and its downstream signaling pathways could be potential therapeutic targets for ASO treatment.